2007
DOI: 10.1021/jp066579q
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Kinetic Modeling of Iron Nanoparticle Synthesis from the Decomposition of Fe(CO)5

Abstract: A detailed chemical kinetic model for gas-phase synthesis of iron nanoparticles is presented in this work. The thermochemical data for Fe n clusters (n g 2), iron carbonyls, and iron-cluster complexes with CO were computed using density functional theory at the B3PW91/6-311+G(d) level of theory. Chemically activated and fall-off reaction rates were estimated by the QRRK method and three-body reaction theory. Kinetic models were developed for two pressures (0.3 and 1.2 atm) and validated against literature shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 42 publications
1
66
1
Order By: Relevance
“…The poor thermal stability of the Fe(CO) 5 (the halflife for decomposition at 300 8C is 5.3 ms [115] ) caused the homogenous nucleation of nanoparticles in the gas phase. [116] These particles were then subjected to a thermophoretic force which limited their approach to the hot substrate and resulted in fractal-like cauliflower structures characteristic of a diffusionlimited aggregation mechanism (in contrast to surface reaction-limited). [65] In 2006 Kay et al reported APCVD films opti- 442 www.chemsuschem.org mized with a substrate temperature of 420 8C and using a carrier gas flow rate of 2 L min…”
Section: Atmospheric Pressure Chemical Vapor Depositionmentioning
confidence: 99%
“…The poor thermal stability of the Fe(CO) 5 (the halflife for decomposition at 300 8C is 5.3 ms [115] ) caused the homogenous nucleation of nanoparticles in the gas phase. [116] These particles were then subjected to a thermophoretic force which limited their approach to the hot substrate and resulted in fractal-like cauliflower structures characteristic of a diffusionlimited aggregation mechanism (in contrast to surface reaction-limited). [65] In 2006 Kay et al reported APCVD films opti- 442 www.chemsuschem.org mized with a substrate temperature of 420 8C and using a carrier gas flow rate of 2 L min…”
Section: Atmospheric Pressure Chemical Vapor Depositionmentioning
confidence: 99%
“…Kuwana and Saito (Kuwana & Saito, 2005) have described nano-particle growth from ferrocene in which they provided a two-step catalytic reaction model for the formation of Fe nano-particles. Wen et al Wen et al, 2007) employed a sectional method developed on simultaneous particle and molecule modeling (SPAMM) approach developed by Pope and Howard (Pope & Howard, 1997). In this approach, catalyst particle formation is modeled as reactions, that can be incorporated into a gas-phase reaction mechanism and allow for the simultaneous modeling of the gas-phase chemistry and the nano-particle formation processes.…”
Section: Mathematical Models For Growth Of Cnts In Flamesmentioning
confidence: 99%
“…Most of the physical methods require substrates [2][3][4][5][6]. For the fabrication of perpendicular recording media, substrate is applicable, but for the biological application individual nanoparticles are more reliable.…”
Section: Introductionmentioning
confidence: 99%